Cape Verde : 2008 Article IV Consultation and Fourth Review Under the Policy Support Instrument-Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Cape Verde. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Over the last several years, Cape Verde has achieved a major economic transformation that is a tribute to its sound homegrown economic reform program. This 2008 Article IV Consultation highlights that real per capita GDP in Cape Verde has increased on average by more than 7 percent a year since 2001, faster than most small island economies and the average for sub-Saharan Africa. Policy implementation under the Policy Support Instrument (PSI) is also strong. All PSI quantitative assessment criteria for end-December 2007 were met with wide margins.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet